2020
DOI: 10.1029/2019jd032212
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Polarimetric Radar Characteristics of Heavy Rainfall From Hurricanes Harvey (2017) and Florence (2018)

Abstract: Polarimetric coastal radar data are used to compare the rainfall characteristics of Hurricanes Harvey (2017) and Florence (2018). Intense rainfall was an infrequent yet important contributor to the total rainfall in Harvey, but its relative contribution varied spatially. The total rainfall over land maximized near the coast over Beaumont, TX, due to intense convection resulting from prolonged onshore flow downshear from the circulation center. Overall, polarimetric radar observations in Harvey show a dominance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Wen et al (2018) found that 99% the rainfall in seven landfalling typhoons consisted of raindrops less than 4 mm in diameter. In contrast, the rainbands in Hurricane Harvey (2017) sometimes exhibited large concentrations of medium‐ to large‐sized raindrops (Brauer et al, 2020; DeHart & Bell, 2020; Wolff et al, 2019). Embedded convective cells within TC rainbands can generate locally enhanced concentrations of ice crystals, snow, and some graupel (Kalina et al, 2017; Wang et al, 2018), which can produce larger raindrops in the outer rainbands (Wu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Wen et al (2018) found that 99% the rainfall in seven landfalling typhoons consisted of raindrops less than 4 mm in diameter. In contrast, the rainbands in Hurricane Harvey (2017) sometimes exhibited large concentrations of medium‐ to large‐sized raindrops (Brauer et al, 2020; DeHart & Bell, 2020; Wolff et al, 2019). Embedded convective cells within TC rainbands can generate locally enhanced concentrations of ice crystals, snow, and some graupel (Kalina et al, 2017; Wang et al, 2018), which can produce larger raindrops in the outer rainbands (Wu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Hurricane Laura provided a unique opportunity and novel data set to quantify drop size distribution characteristics in different portions of a landfalling TC using ground radar observations, space‐borne radar retrievals, and disdrometer measurements. Prior research has examined the microphysical signatures in different regions of landfalling TCs using ground and space‐borne radar observations (e.g., Brauer et al., 2021; DeHart & Bell, 2020; Didlake & Kumjian, 2017; Feng & Bell, 2019; Homeyer et al., 2021), however the use of disdrometer observations were not incorporated in order to verify PSD quantities and provide a direct comparison to estimations from remote sensing platforms as these retrievals were unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…This process occurs as smaller drops have a lower terminal velocity and are therefore advected further downwind, whereas larger hydrometeors fall out of the cloud at a faster rate (Kumjian & Ryzhkov, 2012). DeHart and Bell (2020) found that polarimetric radar observations in Hurricane Harvey (2017) and Hurricane Florence (2018) exhibited signatures associated with large concentrations of small and medium drops, with Harvey having the greatest particle size distribution (PSD) variability over time. These are similar to the results from Zheng et al (2021), who also concluded that collision-coalescence and accretion are the dominant processes in mature inner rainbands.…”
mentioning
confidence: 99%
“…The eye was located about 240 km SSW of the Wallops (PRF) at this time and tracking NNE between 6 and 10 m/s. A brief analysis of the hurricane azimuthal asymmetry suggested that the shear vector was directed to the NE and the outer rain bands were located in the down shear left (DL) quadrant [46]. Several studies of hurricanes have shown that stratiform rain occurs in the DL quadrant [5,6] and typically these outer rain bands are sufficiently steady that a 1D model would be sufficient to simulate the microphysical profiles.…”
Section: Overview Of Rain Bands From Radar Observations and 1d Mcsnow Modelmentioning
confidence: 99%